Relationship between organisational justice, counterproductive work behaviour and islamic work ethics in selected ministries in public sector in Oman - Al-Balushi, Sharifa Khamis Salim (Kulliyyah of Economic and Management Sciences, International Islamic University Malaysia, 2014)
Due to their roles in daily life, the phenomena of organisational justice, counterproductive work behaviour, and the relationship between these two phenomena have received extensive attention in numerous past researches. However, most of these studies are from the Western point-of-view. There are very few studies from the Islamic point-of-view. This study reviewed this relationship from the Islamic perspective. In addition, it examined the relationship of the Islamic work ethics with the two phenomena. The data was collected from 609 Muslim employees from three ministries in the public sector in the Sultanate of Oman (399 employees from the Ministry of Education, 113 employees from the Ministry of Civil Service, and 97 from the Ministry of Finance). Three different scales were used to measure the three variables: organisational justice, counterproductive work behaviour, and Islamic work ethics. The results showed that negative employee's perception is related to organisational justice, and positive perception is related to Islamic work ethics and counterproductive work behaviour. Results also indicated that there is no relationship between organisational justice and Islamic work ethics; while there were evidence that suggests employees' higher perception of Islamic work ethics decreases counterproductive work behaviour practices. The result showed there is no significant mediating influence of Islamic work ethics in the relationship between organisational justice and counterproductive work behaviour. Furthermore, the study investigated the negative impact of organisational justice on counterproductive work behaviour. Future studies are suggested to provide deeper insight and understanding on organisational justice, counterproductive work behaviour and Islamic work ethics; which in turn, will enhance better working environment. Finally, the implication of the study was discussed.